A method for preparing a full-solid waste high-strength artificial aggregate of waste incineration fly ash based on disc granulation
Patent Information
- Application Number
- CN202610799196.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-04
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-06-04
AI Technical Summary
[0008]针对现有技术中垃圾焚烧飞灰资源化利用率低、用于制备人造骨料时存在成型率低、飞灰掺量有限、产品强度差以及传统圆盘造粒装置适应性不佳等问题,本发明旨在提供一种基于圆盘造粒的垃圾焚烧飞灰全固废高强度人造骨料制备方法
[0023](1)实现了飞灰的高掺量与全面安全稳定化:本发明将垃圾焚烧飞灰、粉煤灰与粒化高炉矿渣按干基质量份数40~80:10~30:10~30进行配料混合,利用粉煤灰和粒化高炉矿渣中丰富的SiO2、Al2O3与飞灰中高含量CaO协同激发胶凝活性。在此基础上,进一步采用阶梯式养护制度,先在60±5 ℃、相对湿度≥90%的条件下预养护1~7天,再于120~270 ℃、饱和蒸汽压下进行水热养护1~8小时。预养护阶段形成初步固化骨架,水热养护阶段促使活性硅铝组分与钙及重金属离子反应生成水化硅铝酸钙(C-A-S-H)、托勃莫来石等致密矿物相,从而将重金属离子化学键合固定在矿物晶格中。同时,氯盐随饱和蒸汽脱除,二噁英在水热环境下高效分解。最终使垃圾焚烧飞灰掺量可高达50%以上,实现了危险废物从化学本质上的安全、高值化利用。
Smart Images

Figure CN122325137B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of safe disposal and resource utilization of hazardous waste, specifically to a method for preparing high-strength artificial aggregate from waste incineration fly ash solid waste based on disc granulation. Background Technology
[0002] The incineration process produces fly ash, which accounts for approximately 3% to 12% of the incinerated waste. Fly ash has a complex composition, containing not only high concentrations of leached heavy metals (such as Pb, Zn, Cd, Cr, Cu, etc.) and high levels of chloride salts, but also trace amounts of persistent organic pollutants such as dioxins. Therefore, it is generally considered hazardous waste.
[0003] Developing efficient and safe technologies for the resource utilization of fly ash from waste incineration is urgently needed. In recent years, using fly ash as a secondary resource to prepare building materials, such as cementitious admixtures, expanded clay aggregates, and artificial aggregates, has been considered a highly promising approach. Among these, preparing lightweight or ordinary artificial aggregates for use in concrete to replace natural sand and gravel can not only absorb large amounts of fly ash but also alleviate the ecological pressure caused by the mining of natural aggregates, aligning with the development concept of a circular economy.
[0004] However, the chemical composition of fly ash itself is the main bottleneck restricting its high-value-added resource utilization. Fly ash is usually rich in calcium oxide (CaO), but has relatively low content of active silica (SiO2) and alumina (Al2O3), resulting in limited independent hydration and cementitious activity. If used directly to prepare artificial aggregates, it often suffers from difficulties in molding, low green body strength, unstable curing effect on pollutants such as heavy metals and chloride ions, and ineffective degradation of dioxins, posing long-term environmental safety hazards. To prepare artificial aggregates with qualified performance, existing technologies usually adopt two strategies: one is to mix fly ash as a small amount of admixture (usually less than 20%) with cement, clay, and other cementitious materials or matrix materials; the other is to sinter fly ash at high temperature (>1000 ℃) to prepare ceramsite. The former has limited fly ash disposal capacity and insignificant economic and environmental benefits; the latter has disadvantages such as high energy consumption, risk of secondary dioxin emissions, and complex exhaust gas treatment. Therefore, how to achieve high utilization of fly ash in aggregates while ensuring environmental safety, and at the same time meet the requirements of simple production process and excellent product performance, is a prominent technical challenge at present.
[0005] In terms of forming processes, disc pelletizing is widely used in the preparation of artificial aggregates due to its continuous operation and regular particle shape. However, traditional disc pelletizing equipment and processes generally suffer from problems such as low pelletizing rate, poor particle strength, and uneven particle size distribution when processing low-plasticity, low-binding mixtures mainly composed of fly ash. The root cause lies in the insufficient binding and plasticity of fly ash-based mixtures, making it difficult to effectively form and maintain stable particles during the disc rolling process. This directly leads to raw material waste, low production efficiency, and low product qualification rate, severely restricting the industrial application of this technology.
[0006] In summary, the existing technology has the following shortcomings: (1) It lacks effective component regulation and activation technology for the high calcium and low silicon aluminum chemical characteristics of fly ash, making it difficult to achieve high dosage and high activity utilization under the condition of high temperature sintering; (2) The existing disc granulation device and process have poor adaptability to fly ash-based materials, resulting in low molding efficiency and quality; (3) The fly ash-based artificial aggregates prepared often have problems such as low strength and unstable performance, making it difficult to meet the requirements of engineering applications.
[0007] Therefore, there is an urgent need to develop a preparation method and dedicated equipment that can synergistically optimize the raw material ratio, molding process and curing system, so as to achieve safe, high-volume and high-performance resource utilization of waste incineration fly ash. Summary of the Invention
[0008] To address the problems of low resource utilization rate of waste incineration fly ash, low forming rate, limited fly ash content, poor product strength, and poor adaptability of traditional disc granulation equipment in existing technologies, this invention aims to provide a method for preparing high-strength artificial aggregate from waste incineration fly ash using disc granulation. This method aims to achieve high-content, safe, and efficient resource utilization of fly ash, while significantly improving the forming rate and mechanical properties of the aggregate. It also provides a corresponding optimized equipment solution, offering key technical support for the construction of waste-free cities.
[0009] To achieve the above objectives, the present invention adopts the following technical solution:
[0010] This invention provides a method for preparing high-strength artificial aggregate from waste incineration fly ash solid waste based on disc granulation, characterized by comprising the following steps:
[0011] (1) Batching and mixing: The fly ash from waste incineration, fly ash and granulated blast furnace slag are mixed in a dry weight ratio of 40~80:10~30:10~30 to obtain a dry mixture;
[0012] (2) Disc granulation: 0.5% to 2% of the dried mixture is placed in a disc granulator. During the rotation of the disc, water is added evenly in the disc by spraying. Water and dried mixture are added alternately, and the amount of water added is controlled to be 15% to 35% of the mass of the dried mixture to make a shaped aggregate blank with a particle size of 5 to 12 mm.
[0013] (3) Pre-curing: The shaped aggregate preform is cured for 1 to 7 days at 60±5 ℃ and relative humidity ≥90% to obtain pre-cured aggregate preform;
[0014] (4) Hydrothermal curing: The pre-cured aggregate preform is placed in a hydrothermal reactor and cured for 1 to 8 hours at 120 to 270 °C and saturated steam pressure. After cooling, the artificial aggregate derived from waste incineration fly ash is obtained.
[0015] In this process, the pre-curing in step (3) forms a preliminary solidified skeleton with a certain strength for the subsequent reaction; the hydrothermal curing in step (4), under high temperature and high pressure, promotes the reaction between the active silica-alumina components in the mixture and the calcium and heavy metal ions in the fly ash, generating a dense mineral phase mainly composed of calcium aluminosilicate hydrate (CASH) and tobermorite, thereby chemically binding and fixing the heavy metal ions in the mineral lattice. At the same time, chloride salts are removed from the aggregate along with the saturated steam generated by the hydrothermal process, and the high temperature and high pressure hydrothermal environment also provides the necessary conditions for the decomposition of dioxins.
[0016] Preferably, in step (1), the dry basis mass ratio of the waste incineration fly ash, fly ash and granulated blast furnace slag is further preferably 50~70:15~25:15~25.
[0017] Preferably, in step (2), the amount of water added is further preferably 20% to 30% of the mass of the dried mixture.
[0018] Preferably, the disc granulator used in step (2) is optimized as follows: Inside the disc granulator, an arc-shaped liner is provided between the bottom of the disc and the sidewall of the disc for transition. The arc-shaped liner is arranged circumferentially along the inner sidewall of the disc, and the inner surface of the arc-shaped liner is a circular arc surface with a radius of curvature at least twice the depth of the disc. This structure helps improve the rolling trajectory of the mixture, enhances the pelletizing effect, and reduces powder adhesion to the wall.
[0019] Preferably, the arc-shaped liner is made of rubber or metal.
[0020] Preferably, the waste incineration fly ash content in the artificial aggregate derived from waste incineration fly ash is not less than 50%, the compressive strength is not less than 5 MPa, the bulk density is 800~1200 kg / m³, and the water absorption rate is less than 15%.
[0021] It possesses excellent mechanical properties, physical properties, and environmental safety.
[0022] Compared with the prior art, the present invention has the following significant advantages:
[0023] (1) Achieving high fly ash content and comprehensive safety stabilization: This invention mixes waste incineration fly ash, fly ash, and granulated blast furnace slag in a dry weight ratio of 40-80:10-30:10-30. The abundant SiO2 and Al2O3 in fly ash and granulated blast furnace slag, along with the high CaO content in fly ash, synergistically stimulate cementitious activity. Based on this, a stepped curing system is further adopted: pre-curing for 1-7 days at 60±5 ℃ and relative humidity ≥90%, followed by hydrothermal curing for 1-8 hours at 120-270 ℃ and saturated steam pressure. The pre-curing stage forms a preliminary solidified framework, while the hydrothermal curing stage promotes the reaction of active silica-alumina components with calcium and heavy metal ions to generate dense mineral phases such as hydrated calcium aluminosilicate (CASH) and tobermorite, thereby chemically binding and fixing heavy metal ions in the mineral lattice. Simultaneously, chloride salts are removed with saturated steam, and dioxins decompose efficiently under hydrothermal conditions. Ultimately, the fly ash content of waste incineration can reach more than 50%, realizing the safe and high-value utilization of hazardous waste from a chemical perspective.
[0024] (2) Significantly improved molding rate and aggregate mechanical properties: In this invention, an arc-shaped liner is set around the inner wall of the bottom of the disc of the disc pelletizer. The radius of curvature of the arc surface of the inner surface of the arc-shaped liner is at least twice the depth of the disc. This structure improves the rolling trajectory of the low-plasticity fly ash-based mixture, reduces powder adhesion to the wall, and enhances the pelletizing effect. During pelleting, the water content is controlled at 15%~35% of the dry mixture mass, and water and mixture are added alternately to produce preforms with a particle size of 5~12 mm. Combined with the above-mentioned pre-curing and hydrothermal curing system, the molding rate can be increased to over 90%, the compressive strength of the artificial aggregate can be stably reached over 5 MPa, and the bulk density can be controlled at 800~1200 kg / m³. 3 The water absorption rate is less than 15%.
[0025] (3) Strong process synergy and outstanding environmental and economic benefits: This invention systematically integrates raw material composition optimization, molding device improvement, and stepped curing system to form a non-sintering, low-energy-consumption preparation path. Among them, raw material composition optimization refers to the proportion design of fly ash, fly ash, and slag; molding device improvement refers to setting up arc-shaped liners with specific curvature; and stepped curing system refers to pre-curing plus hydrothermal curing. The entire process does not require the addition of cement or other chemical curing agents, and the entire process utilizes the inherent activity and thermal energy of solid waste. This invention not only efficiently disposes of various solid wastes such as waste incineration fly ash, fly ash, and granulated blast furnace slag, but also produces artificial aggregates with performance comparable to natural aggregates, providing a solution for zero-waste city construction that combines environmental benefits and engineering feasibility.
[0026] The features and advantages of the present invention will be described in detail through embodiments and in conjunction with the accompanying drawings. Attached Figure Description
[0027] Figure 1 This is a process flow diagram of the method for preparing artificial aggregate derived from waste incineration fly ash according to the present invention;
[0028] Figure 2 This is a schematic diagram of the conventional disc granulator structure before optimization in this invention;
[0029] In the diagram: 1. Disc; 2. Frame; 3. Connecting frame; 4. Scraper.
[0030] Figure 3 This is a schematic diagram of the optimized disc granulator structure in this invention;
[0031] In the diagram: 1. Disc; 2. Frame; 3. Connecting frame; 4. Scraper; 5. Arc-shaped liner.
[0032] Figure 4 This is a schematic diagram of the cross-sectional structure of the disc in the optimized disc granulator of the present invention;
[0033] In the diagram: 1. Circular disk; 5. Arc-shaped liner.
[0034] Figure 5 This is a scanning electron microscope (SEM) image of the artificial aggregate prepared according to preferred embodiment 2 of the present invention.
[0035] In the diagram: 6. hydrated calcium aluminosilicate; 7. Tobermullite.
[0036] Figure 6 This is a bar chart comparing the compressive strength of the artificial aggregates prepared in the embodiments and comparative examples of the present invention. Detailed Implementation
[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the embodiments of this invention will be described in detail below with reference to the accompanying drawings. It should be noted that the embodiments described below are only for explaining this invention and are not intended to limit it. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0038] This invention addresses the challenge of resource utilization of fly ash from waste incineration by innovatively proposing a system solution that combines raw material synergy, process coupling, and equipment optimization. The technical solution and significant effects of this invention will be described in detail below through specific embodiments and comparative examples. Unless otherwise specified, the reagents, equipment, and methods used in this invention are all conventional choices in this technical field.
[0039] Example 1
[0040] This embodiment aims to verify the basic technical solution of the present invention and the technical effect of the optimized device. Figure 1 This is a process flow diagram of the method for preparing artificial aggregate derived from waste incineration fly ash according to the present invention, which includes the following steps:
[0041] (1) Batching and mixing: Weigh the waste incineration fly ash, fly ash and granulated blast furnace slag according to dry basis weight: 60 parts waste incineration fly ash, 20 parts fly ash and 20 parts granulated blast furnace slag (total of 100 parts). Mix them evenly in a mixer to obtain a dry mixture;
[0042] (2) Disc (1) Granulation: 1% of the above-mentioned dried mixture is first added to the optimized and modified disc granulator. To facilitate understanding of the improvements of this invention, the structure of a conventional disc granulator is briefly described first. Figure 2 As shown, a conventional disc granulator includes an inclined disc (1), with a frame (2) below the disc (1). The frame (2) is connected to the disc (1) and supports its rotation. A motor that drives the disc (1) to rotate is mounted on the frame (2) or on the ground. A connecting frame (3) for mounting scrapers (4) is installed on the frame (2). The scrapers (4) are used to scrape off materials adhering to the bottom and sides of the disc to prevent material accumulation. Based on this, the present invention optimizes the disc granulator, such as... Figure 3 As shown, the optimized disc granulator also includes a disc (1), a frame (2), a connecting frame (3), and a scraper (4). The difference is that an arc-shaped liner (5) is provided between the bottom of the disc (1) and the side wall of the disc (1) for transition. It is made of stainless steel and the arc-shaped liner (5) is arranged circumferentially along the inner side wall of the side wall of the disc (1). Figure 4The cross-sectional structure of the disc (1) is further shown, and the arc-shaped liner (5) is more clearly visible attached to the bottom of the inner wall of the disc (1), with a radius of curvature approximately twice the depth of the disc (1). The function of the arc-shaped liner (5) is to improve the rolling trajectory of the material within the disc (1), promote the compact packing of particles, and thus improve the pelleting rate and compactness of the pellets. During the rotation of the disc (1), water is uniformly added to the disc (1) by spraying, and water and dry mixture are added alternately, with the amount of water added controlled to be 30% of the total mass of the dry mixture. Granulation is continued for about 12 minutes, and the formed aggregate pellets with a particle size between 5 and 12 mm are collected by sieving, and the forming rate is recorded to be approximately 88%.
[0043] (3) Pre-curing: The shaped aggregate blanks are placed in a constant temperature and humidity curing chamber and cured for 3 days at 60 ℃ and 95% relative humidity to obtain pre-cured aggregate blanks;
[0044] (4) Hydrothermal curing: The pre-cured aggregate blanks are loaded into a hydrothermal reactor and cured for 6 hours at 200 °C and corresponding saturated steam pressure. After cooling, they are taken out to obtain the finished artificial aggregate derived from waste incineration fly ash.
[0045] The finished aggregate was characterized by the following properties: compressive strength of 6.5 MPa, water absorption rate of 15%, and bulk density of 1090 kg / m³. 3 Compared with the conventional disc pelletizer, this embodiment uses an optimized disc pelletizer, which increases the forming rate from about 70% to 89% and the cylinder compressive strength from 4.8 MPa to 6.5 MPa, indicating that the setting of the arc-shaped liner (5) significantly improves the pelletizing effect and aggregate mechanical properties.
[0046] In addition, to verify environmental safety, the finished aggregate products were tested in accordance with national standards. The heavy metal leaching toxicity test (based on HJ / T 557) showed that the leaching concentrations of Pb, Zn, Cd, Cr, and Cu were 0.002 mg / L, 0.025 mg / L, 0.002 mg / L, 0.006 mg / L, and 0.001 mg / L, respectively, all lower than the limits in the "Integrated Wastewater Discharge Standard GB 8978-1996"; the soluble chlorine content (based on HJ / T 557) was 0.017%, lower than the limit of 0.02% in "Lightweight Aggregates and Their Test Methods GB / T 17431.1-2010"; and the dioxin toxicity equivalent concentration (based on HJ 77.3) was 19.43 ng I-TEQ / kg, meeting the limit requirement of less than 50 ng I-TEQ / kg in the "Technical Specification for Pollution Control of Fly Ash from Municipal Solid Waste Incineration HJ 1134-2020". The above data shows that the optimized disc (1) granulation device of the present invention can produce high-performance and environmentally safe aggregate products under the basic proportion.
[0047] Example 2
[0048] This embodiment, based on Embodiment 1, employs optimized proportions and water addition amounts to verify the synergistic effect of raw material proportions, process parameters, and optimized equipment, including the following steps:
[0049] (1) Batching and mixing: Weigh the waste incineration fly ash, fly ash and granulated blast furnace slag according to dry basis weight: 55 parts waste incineration fly ash, 22.5 parts fly ash and 22.5 parts granulated blast furnace slag. Mix evenly to obtain a dry mixture;
[0050] (2) Disc (1) Granulation: The same optimized disc granulator as in Example 1 was used. 1% of the dry mixture was added to the optimized disc granulator, with the water content controlled at 25%, and the granulation time was approximately 12 minutes. Aggregate preforms of 5-12 mm were collected, and the preformation rate was significantly increased to 92%.
[0051] (3) Pre-curing and hydrothermal curing: Same as in Example 1.
[0052] The finished aggregate was characterized for performance, showing a compressive strength of 7.2 MPa, a water absorption rate reduced to 14%, and a bulk density of 1100 kg / m³. 3 . Figure 5 The image shows the microstructure of the artificial aggregate prepared in this embodiment under a scanning electron microscope (SEM). A large amount of hydrated calcium aluminosilicate (6) and tobermulite (7) can be seen in the image, which are interwoven and densely filled.
[0053] Environmental safety testing showed that the finished aggregate exhibited optimal solidification of heavy metals, with leaching concentrations far below standard limits. The leaching concentrations of Pb, Zn, Cd, Cr, and Cu were 0.001 mg / L, 0.016 mg / L, 0.002 mg / L, 0.004 mg / L, and 0.001 mg / L, respectively; the soluble chlorine content was 0.013%; and the dioxin toxicity equivalent concentration was 15.71 ng I-TEQ / kg, reaching optimal levels. All environmental indicators met optimal levels. This fully demonstrates that by employing a synergistic strategy of optimized proportions and granulation equipment, not only were the physical and mechanical properties significantly improved, but the formation of a denser and more uniform hydration product structure greatly enhanced the system's ability to chemically fix and physically encapsulate pollutants, achieving a simultaneous leap in engineering performance and environmental safety.
[0054] Example 3
[0055] This embodiment demonstrates that, within all the preferred parameter ranges protected by this invention, a high-performance aggregate product can still be obtained even with an increased content of fly ash from waste incineration, including the following steps:
[0056] (1) Batching and mixing: Weigh the waste incineration fly ash, fly ash and granulated blast furnace slag according to dry basis weight: 65 parts waste incineration fly ash, 17.5 parts fly ash and 17.5 parts granulated blast furnace slag. Mix evenly to obtain a dry mixture;
[0057] (2) Disc (1) Granulation: The same optimized disc granulator as in Example 1 was used. The water content was controlled at 30%, and the granulation yielded a uniformly sized embryo with a molding rate of 94%.
[0058] (3) Pre-curing: Curing at 62 ℃ and 98% humidity for 2 days;
[0059] (4) Water heat curing: Curing at 220 ℃ for 5 hours.
[0060] The finished aggregate was characterized for its properties. Despite a fly ash content as high as 65%, the finished aggregate maintained excellent compressive strength of 6.8 MPa, a water absorption rate of 13%, and a bulk density of 1020 kg / m³. 3 All of them meet the product performance requirements.
[0061] Environmental safety testing showed that even at the highest fly ash content, the heavy metal leaching concentrations remained fully compliant, with leaching concentrations of Pb, Zn, Cd, Cr, and Cu at 0.002 mg / L, 0.021 mg / L, 0.001 mg / L, 0.005 mg / L, and 0.001 mg / L, respectively; the soluble chlorine content was 0.011%; and the dioxin toxicity equivalent concentration was 17.94 ng I-TEQ / kg. This demonstrates that within the parameter system provided by this invention, even with the fly ash content of incinerated waste increased to a high level of 65%, optimized equipment and processes can still ensure effective stabilization of pollutants, resulting in extremely low environmental risk to the product.
[0062] Comparative Example 1:
[0063] The operation process of this comparative example is consistent with that of Example 1, except that granulated blast furnace slag is not added, which aims to illustrate the necessity of component synergy, and includes the following steps:
[0064] (1) Batching and mixing: Weigh the waste incineration fly ash and fly ash according to dry basis weight: 60 parts waste incineration fly ash, 40 parts fly ash. Ungranulated blast furnace slag. Mix evenly to obtain a dry mixture;
[0065] (2) Disc (1) Granulation: The same optimized disc granulator as in Example 1 was used, with 30% water added, but molding was difficult, the molding rate was only 40%, and the embryo was loose;
[0066] (3) Pre-curing and hydrothermal curing: Same as in Example 1.
[0067] The properties of the finished aggregate were characterized. The obtained aggregate had extremely low strength, was easily dispersed when exposed to water, and had a compressive strength of <1.0 MPa.
[0068] Environmental safety testing showed that the leaching concentrations of Pb, Zn, Cd, Cr, and Cu were 1.103 mg / L, 0.067 mg / L, 0.003 mg / L, 0.017 mg / L, and 0.047 mg / L, respectively, with the Pb leaching concentration exceeding the standard limit. The soluble chlorine content was 0.01%, and the dioxin toxicity equivalent concentration was 20.01 ng I-TEQ / kg. Because the samples could not be formed into complete particles and lacked a dense mineral phase encapsulation, the risk of heavy metal leaching was high. This comparison demonstrates that even with optimized equipment, without the active silica-alumina source provided by granulated blast furnace slag, it is still impossible to form a stable solidified body to achieve safe encapsulation of pollutants.
[0069] Comparative Example 2:
[0070] This comparative example aims to verify the key role of pre-curing, and includes the following steps:
[0071] (1) Ingredient preparation, mixing and granulation: The steps are exactly the same as in Example 2, and the molding rate is 90%.
[0072] (2) Curing: The pre-curing step is omitted, and the molded body is directly subjected to hydrothermal curing (200 ℃, 6 hours).
[0073] The properties of the finished aggregate were characterized. It was found that a large number of aggregate fragments cracked or pulverized during the hydrothermal process, resulting in a low yield. The finished aggregate had a cylinder compressive strength of only 3.1 MPa, numerous internal cracks, a water absorption rate of 18%, and a bulk density of 970 kg / m³. 3 This illustrates that pre-curing is crucial for achieving initial strength and preventing rapid hydrothermal damage.
[0074] Environmental safety testing showed that the leaching concentrations of Pb, Zn, Cd, Cr, and Cu were 1.382 mg / L, 0.013 mg / L, 0.003 mg / L, 0.006 mg / L, and 0.002 mg / L, respectively, with the Pb leaching concentration exceeding the standard limit. The soluble chlorine content was 0.018%, and the dioxin toxicity equivalent concentration was 16.83 ng I-TEQ / kg. This indicates that the preliminary hydration product network formed during pre-curing provides the preform with the necessary initial strength to withstand the severe impact of high-temperature and high-pressure steam during the subsequent hydrothermal curing stage. Without this step, the preform structure is damaged in the early stages of hydrothermal treatment, resulting in incomplete internal reactions, a loose structure with many defects, low strength, and the provision of pathways for heavy metal leaching, thus rendering the curing effect ineffective.
[0075] Comparative Example 3:
[0076] This comparative example aims to demonstrate the necessity of the curved liner. The raw material ratio and curing regime are the same as in Example 1, except that a conventional disc granulator with a flat steel plate bottom is used without any curved liner.
[0077] During the granulation process, the material slid at the bottom of the pan instead of being effectively lifted and rolled down, resulting in a high concentration of fine powder, poor pellet formation, and a molding rate of only 65%. After subsequent curing, the finished aggregate had a cylinder compressive strength of 4.8 MPa, a water absorption rate of 17%, and a bulk density of 1040 kg / m³. 3 Compared with Example 1, under the same formulation and curing regime, due to the lack of the arc-shaped liner, the molding rate decreased from 89% to 70%, and the cylinder compressive strength decreased from 6.5 MPa to 4.8 MPa.
[0078] Environmental safety testing showed that the leaching concentrations of Pb, Zn, Cd, Cr, and Cu were 0.002 mg / L, 0.015 mg / L, 0.001 mg / L, 0.003 mg / L, and 0.002 mg / L, respectively; the soluble chlorine content was 0.015%; and the dioxin toxicity equivalent concentration was 16.09 ng I-TEQ / kg, indicating that the pollutant control effect met the standards. Although the environmental indicators were compliant, as can be seen from Comparative Example 1, this comparative example demonstrates that the optimized disc granulator of this invention, by adding an arc-shaped liner, significantly improved the pellet quality and embryo density, making a direct and positive contribution to improving the overall performance of the final product.
[0079] Comparative Example 4:
[0080] This comparative example aims to verify the adverse effects of an excessively small radius of curvature (i.e., an excessively steep curvature) of the arc-shaped liner (5) on the granulation effect. The operation process is the same as in Example 2, except that the radius of curvature of the installed arc-shaped liner (5) is only 1.0 times the depth of the disc (1). The device still has Figure 3 , Figure 4 The basic structure shown is the same, but the radius of curvature of the arc-shaped liner (5) is smaller than the preferred range of the present invention. The raw material ratio is the same as in Example 2, and the curing system is the same as in Example 2.
[0081] During the granulation process, a large amount of the mixture adhered to the surface of the curved liner, forming a thick scale that was difficult to roll off effectively. The pelleting qualification rate was only 58%, and the resulting pellets were irregular in shape, with some being flat. After subsequent curing, the finished aggregate had a cylinder compressive strength of only 3.5 MPa, a water absorption rate of 20%, and a bulk density of 980 kg / m³. 3 .
[0082] Environmental safety testing showed that the leaching concentrations of Pb, Zn, Cd, Cr, and Cu were 0.021 mg / L, 0.043 mg / L, 0.002 mg / L, 0.009 mg / L, and 0.008 mg / L, respectively; the soluble chlorine content was 0.019%; and the dioxin toxicity equivalent concentration was 21.34 ng I-TEQ / kg. Although these values were still within the standard limits, they were significantly higher than those in Example 2. This indicates that an excessively small radius of curvature can lead to severe adhesion of the material to the wall, making it difficult to form balls, which in turn affects the density of the subsequent curing products and ultimately reduces the mechanical properties and environmental safety of the products.
[0083] Comparative Example 5:
[0084] This comparative example aims to verify the applicability of ordinary carbon steel lining plates in humid environments. The operation process is the same as in Example 2, except that the arc-shaped lining plate is made of ordinary carbon steel, with a radius of curvature 2.0 times the depth of the disk (1), and no rust-proof treatment is applied to the surface. The structure of the device remains the same. Figure 3 , Figure 4 As shown, the material of the arc-shaped liner (5) is ordinary carbon steel. The raw material ratio is the same as in Example 2, and the curing system is the same as in Example 2.
[0085] During the granulation process, continuous water spraying was required, and noticeable rust spots began to appear on the carbon steel liner surface after 6 hours of operation. The rust spots resulted in uneven surface roughness of the liner, severe material adhesion, and a pelleting qualification rate of only 83%. Furthermore, rust mixed into the aggregate blanks, causing reddish-brown spots on the surface of the finished aggregate, affecting its appearance quality. After subsequent curing, the finished aggregate had a cylinder compressive strength of 5.4 MPa, a water absorption rate of 17%, and a bulk density of 1040 kg / m³. 3 .
[0086] Environmental safety testing showed that iron ion leaching led to a higher background value of Fe element in the finished aggregate heavy metal test. Although it did not exceed the relevant limits, the purity of the product was affected. The soluble chlorine content was 0.016%, and the dioxin toxicity equivalent concentration was 17.43 ng I-TEQ / kg. The results indicate that ordinary carbon steel is unsuitable for granulation environments requiring continuous spray water addition due to its poor corrosion resistance. This invention preferably uses stainless steel or wear-resistant steel liners, which can ensure both effective pelletizing and meet the durability requirements for long-term operation.
[0087] Performance comparison analysis:
[0088] The key performance data of the above embodiments and comparative examples are summarized in the table below, and an intensity comparison chart is drawn. Figure 6 ).
[0089] Table 1. Performance Comparison of Examples and Comparative Examples
[0090]
[0091] Environmental safety comparative analysis:
[0092] The key environmental safety indicators of the above embodiments and comparative examples are summarized in the table below for comprehensive analysis.
[0093] Table 2 Comparison of Environmental Safety Indicators between Examples and Comparative Examples
[0094]
[0095] As can be seen from the above systematic embodiments and comparative examples, the present invention can produce high-strength, environmentally safe waste incineration fly ash-derived artificial aggregates through the synergistic effect of a specific raw material ratio, an optimized granulation device including an arc-shaped liner (5), and a stepped curing process of pre-curing and hydrothermal curing. It not only successfully solves the engineering problems of low forming rate and insufficient strength of fly ash-based artificial aggregates, but also simultaneously achieves efficient and stable solidification and degradation of core pollutants such as heavy metals, chlorides, and dioxins.
Claims
1. A method for preparing high-strength artificial aggregate from waste incineration fly ash solid waste based on disc granulation, characterized in that, Includes the following steps: 1) Batching and mixing: The waste incineration fly ash, fly ash and granulated blast furnace slag are mixed in a dry weight ratio of 50~70:15~25:15~25 to obtain a dry mixture; 2) Disc granulation: 0.5% to 2% of the dried mixture is placed in a disc granulator. During the rotation of the disc, water is added evenly inside the disc by spraying. Water and dried mixture are added alternately, and the amount of water added is controlled to be 15% to 35% of the mass of the dried mixture, so as to produce shaped aggregate blanks with a particle size of 5 to 12 mm. Inside the disc granulator, there is an arc-shaped liner between the bottom of the disc and the side wall of the disc. The arc-shaped liner is arranged circumferentially along the inner side wall of the disc. The inner surface of the arc-shaped liner is an arc surface, and the radius of curvature of the arc surface is at least twice the depth of the disc. 3) Pre-curing: The shaped aggregate preform is cured at 60±5 ℃ and relative humidity ≥90% for 1~7 days to obtain pre-cured aggregate preform; 4) Hydrothermal curing: The pre-cured aggregate preform is placed in a hydrothermal reactor and cured at 200~270 ℃ and saturated steam pressure for 1~8 hours to obtain the artificial aggregate derived from waste incineration fly ash.
2. The preparation method according to claim 1, characterized in that: In step (2), the amount of water added is 20% to 30% of the mass of the dried mixture.
3. The preparation method according to claim 2, characterized in that: The arc-shaped liner is made of rubber or metal.
4. The preparation method according to claim 3, characterized in that: The waste incineration fly ash content in the artificial aggregate derived from waste incineration fly ash is not less than 50%, the compressive strength is not less than 5 MPa, the bulk density is 800~1200 kg / m³, and the water absorption rate is less than 15%.
Citation Information
Patent Citations
Artificial aggregate and preparation method thereof
CN110872185A
Preparation method of high-content and high-strength fly ash non-sintered ceramsite
CN112745071A
Method for preparing all-solid-waste-based non-sintered ceramsite by synergistically recycling solid wastes
CN119707334A
Garbage incineration fly ash artificial aggregate and preparation method thereof
CN121135274A